2011
DOI: 10.1123/jpah.8.s1.s17
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and Barriers to Adopting Evidence-Based Physical Education in Elementary Schools

Abstract: To facilitate EBPE adoption, dissemination efforts should target both principals and PE teachers. Increasing principal's knowledge may be instrumental in addressing some teacher perceptions of barriers to PE. Strategic advocacy efforts, including targeting policies that require PE program evaluation, are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 27 publications
(36 reference statements)
3
46
0
1
Order By: Relevance
“…For example, in a study in the US, McKenzie (2007b) complained that physical educators are rarely trained to be effective in teaching behavioural skills, promoting physical activity beyond the gymnasium, or doing the kind of social marketing required to encourage sustained physical activity engagement. Furthermore, a study by Lounsbery, McKenzie, Trost & Smith (2011) argued that a lack of critical awareness and accountability in schools presented persistent barriers to the dissemination and adoption of evidence-based health-PE programmes. In Germany, it was reported that few PE programmes focus on health in any systematic or specialised way and that PE teachers tend to focus on developing young people"s sporting abilities.…”
Section: Towards the Development Of New 'Pe-for-health' Pedagogiesmentioning
confidence: 99%
“…For example, in a study in the US, McKenzie (2007b) complained that physical educators are rarely trained to be effective in teaching behavioural skills, promoting physical activity beyond the gymnasium, or doing the kind of social marketing required to encourage sustained physical activity engagement. Furthermore, a study by Lounsbery, McKenzie, Trost & Smith (2011) argued that a lack of critical awareness and accountability in schools presented persistent barriers to the dissemination and adoption of evidence-based health-PE programmes. In Germany, it was reported that few PE programmes focus on health in any systematic or specialised way and that PE teachers tend to focus on developing young people"s sporting abilities.…”
Section: Towards the Development Of New 'Pe-for-health' Pedagogiesmentioning
confidence: 99%
“…For example, Lanier et al [101] found that teachers were often unaware of their respective school's wellness policies, and two studies identified the school principals' leadership as key to improved physical activity and nutrition policy implementation [102,103]. One study identified that lower complexity, higher compatibility, and greater perceived relative advantage assisted schools in implementing nutrition guidelines [104].…”
Section: Policy Issuesmentioning
confidence: 99%
“…This is of note, given that the control groups in these studies received the same time in PE or "dose" as the intervention group and both intervention and control groups had PE specialists deliver the respective programs. Given the issues identified in primary school PE internationally, including the constraints of a "crowded curriculum" [60][61][62][63] , further strategies to integrate FMS learning beyond the school may have merit. This was a successful strategy used in 4 studies in the after-school setting 35,37,42,45 and by using supplementary home-based FMS tasks.…”
Section: Fms Intervention Characteristics and Pedagogical Approachesmentioning
confidence: 99%